PELATIHAN PEMANFAATAN MEDIA SOSIAL DAN BLOG SEBAGAI SARANA PUBLIKASI BUSTANUL ATHFAL KABUPATEN PONROOGO - Muhibuddin Fadhli; M. Fadlilah (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2017)
Social media becomes one of the things that must be mastered and utilized well by institutions that want to publish their activities. Social media should also be used well and wisely. The methods used in this training are mentoring and peer tutors with material expectations that can be well received. The training is intended to provide insight into the proper use of social media so that it can provide benefits for the self. The participants of this training are the representatives of Bustanul Athfal (BA) teachers in Ponorogo District. There are 15 agencies involved in this training with the results of participants who have social media accounts of the institution and blogs that can be used as a publication medium.